Clusterin knockdown sensitizes prostate cancer cells to taxane by modulating mitosis. Issue 7 (19th May 2016) - Al Nakouzi, Nader; Wang, Chris Kedong; Beraldi, Eliana; Jager, Wolfgang; Ettinger, Susan; Fazli, Ladan; Nappi, Lucia; Bishop, Jennifer; Zhang, Fan; Chauchereau, Anne; Loriot, Yohann; Gleave, Martin
Abstract: Clusterin (CLU) is a stress‐activated molecular chaperone that confers treatment resistance to taxanes when highly expressed. While CLU inhibition potentiates activity of taxanes and other anti‐cancer therapies in preclinical models, progression to treatment‐resistant disease still occurs implicating additional compensatory survival mechanisms. Taxanes are believed to selectively target cells in mitosis, a complex mechanism controlled in part by balancing antagonistic roles of Cdc25C and Wee1 in mitosis progression. Our data indicate that CLU silencing induces a constitutive activation of Cdc25C, which delays mitotic exit and hence sensitizes cancer cells to mitotic‐targeting agents such as taxanes. Unchecked Cdc25C activation leads to mitotic catastrophe and cell death unless cells up‐regulate protective mechanisms mediated through the cell cycle regulators Wee1 and Cdk1. In this study, we show that CLU silencing induces a constitutive activation of Cdc25C via the phosphatase PP2A leading to relief of negative feedback inhibition and activation of Wee1‐Cdk1 to promote survival and limit therapeutic efficacy. Simultaneous inhibition of CLU‐regulated cell cycle effector Wee1 may improve synergistic responses of biologically rational combinatorial regimens using taxanes and CLU inhibitors. Synopsis: CLU silencing sensitizes prostate cancer cells to taxane by inducing a constitutive activation of Cdc25C leading to a delay in exit from mitosis. In response, cells up‐regulate protective mechanisms through Wee1 kinase. CLU expression and Cdc25C expression are negatively correlated in prostate cancer cell lines, mice xenografts, and human biopsies. CLU silencing induces accumulation of Cdc25C‐T48 phosphorylation. Constitutive activation of Cdc25C by CLU silencing is compensated by Wee1 up‐regulation. CLU silencing sensitizes PC3 cells to cabazitaxel, and inhibition of Wee1 improves synergistic responses to combination of taxanes and CLU inhibitors. Abstract : CLU silencing sensitizes prostate cancer cells to taxane by inducing a constitutive activation of Cdc25C leading to a delay in exit from mitosis. In response, cells up‐regulate protective mechanisms through Wee1 kinase.